Glutamate Induces Apoptosis in Anterior Pituitary Cells through Group II Metabotropic Glutamate Receptor Activation - Bottino, Maria Cecilia (2004)
Glutamate can induce neuronal cell death by activating ionotropic glutamate receptors (iGluRs) as well as metabotropic glutamate receptors (mGluRs). In the present study, we investigated whether glutamate induces apoptosis of cultured anterior pituitary cells from female rats. Glutamate (1 mM) significantly reduced the metabolic activity of viable cells and increased the percentage of terminal deoxynucleotidyl transferasemediated deoxyuridine triphosphate nick-end labeling (TUNEL)-positive cells and caspase-3 activity in anterior pituitary cells. The inhibitory effect of glutamate on the viability of anterior pituitary cells was not observed in the presence of [2S]-α-ethylglutamic acid (0.75 mM), a specific group II mGluR antagonist. Also, (2S,1′S,2′S)-2-(carboxycyclopropyl) glycine (LCCG-I; 0.75 mM), a specific group II mGluR agonist, reduced viability and increased the percentage of TUNEL-positive anterior pituitary cells. Group I and III mGluRs and iGluRs agonists failed to modify the metabolic activity of anterior pituitary cells. Glutamate and LCCG-I increased the percentage of TUNEL-positive lactotropes and somatotropes. The subunit mGluR2/3, belonging to group II mGluR, was localized in these cell types. Glutamate increased nitric oxide (NO) synthase (NOS) activity and inducible NOS expression in anterior pituitary cells. N-methyl-L-arginine (NMMA, 0.5 mM), a NOS inhibitor, potentiated the apoptotic effect of glutamate in anterior pituitary cells, indicating that NO may restrain glutamate-induced apoptosis. Incubation of anterior pituitary cells with a cAMP analog (N6, 2′-o-dibutyryladenosine 3′, 5′-cyclic monophosphate; 1 mM) attenuated the apoptosis induced by glutamate. Glutamate and LCCG-I decreased prolactin release from anterior pituitary cells. N6, 2′-o-dibutyryladenosine 3′, 5′-cyclic monophosphate reversed the inhibitory effect of glutamate on prolactin release, but NMMA failed to modify it. Our data show that glutamate induces apoptosis of lactotropes and somatotropes through group II mGluR activation, probably by decreasing cAMP synthesis.